COMPOUNDING STERILE PREPARATIONS FOR INTENSIVE CARE UNIT PATIENTS (ICU) IN ONE PRIVATE HOSPITAL IN SEMARANG - Sara Septi Widayani; Sri Hartati Yuliani; Dina Christin Ayuning Putri (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2018)
Sterile preparations for intravenous injection probably cause greater risk of errors than other preparation treatment routes due to their complex preparation steps. Errors in preparation and compounding stage will affect the quality and stability of the pharmaceutical product obtained. The aim of this study was to evaluate the process of compounding and assess both quality and stability of the parenteral preparations products that resulted from the compounding process for ICUs patients in one private hospital in Semarang, Central Java, Indonesia. This observational analytic study was conducted using accidental sampling technique. The descriptive study results showed that sterile preparation in hospital X was not performed according to the Guidelines for Drug Injection and Handling of Cytostatic Preparations. In order to evaluate the quality of the sterile preparations, three different drugs with the highest prevalence of use: namely ceftriaxone, meropenem and omeprazole were evaluated. It was found that the pH value of omeprazole was not acceptable due to the use of an appropriateness solvent. The sterility tests showed that the preparation products prepared by the nurses were free from microorganisms.